2008
DOI: 10.1210/jc.2007-2138
|View full text |Cite
|
Sign up to set email alerts
|

Hyperghrelinemia Precedes Obesity in Prader-Willi Syndrome

Abstract: Plasma ghrelin levels in children with PWS are elevated at any age, including during the first years of life, thus preceding the development of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 34 publications
5
96
0
2
Order By: Relevance
“…Some studies have shown elevated ghrelin levels in PWS infants and children and thus it appears that hyperghrelinemia may precede hyperphagia in PWS, though this has not been universally seen in all studies (Erdie-Lalena et al, 2006;Feigerlova et al, 2008;Haqq et al, 2008). Neonatal transgenic deletion PWS mice die from severe neonatal hypoglycemia due to depletion of liver glycogen stores, and ghrelin levels increase reciprocally with the falling glucose levels (Stefan et al, 2005) Although it has been hypothesised that hyperphagia in PWS may be partly explained by rapid gastric emptying due to increased gastric motility caused by elevated ghrelin levels, in fact patients with PWS have delayed gastric emptying (Choe et al,…”
mentioning
confidence: 99%
“…Some studies have shown elevated ghrelin levels in PWS infants and children and thus it appears that hyperghrelinemia may precede hyperphagia in PWS, though this has not been universally seen in all studies (Erdie-Lalena et al, 2006;Feigerlova et al, 2008;Haqq et al, 2008). Neonatal transgenic deletion PWS mice die from severe neonatal hypoglycemia due to depletion of liver glycogen stores, and ghrelin levels increase reciprocally with the falling glucose levels (Stefan et al, 2005) Although it has been hypothesised that hyperphagia in PWS may be partly explained by rapid gastric emptying due to increased gastric motility caused by elevated ghrelin levels, in fact patients with PWS have delayed gastric emptying (Choe et al,…”
mentioning
confidence: 99%
“…However, this conclusion is contradicted by the largest study that found elevated fasting plasma ghrelin levels in PWS children under 3 years. 47 It is possible that these discrepancies are related to the smaller size of the negative studies, including our own. 39,42,46 Furthermore, hyperghrelinaemia in older children and PWS adults may be partially, though not solely, explained by preserved insulin sensitivity and relative hypoinsulinaemia, as ghrelin levels are negatively correlated with insulin.…”
Section: Ghrelinmentioning
confidence: 86%
“…14 By contrast, in a larger and younger study cohort of 40 children and adolescents with PWS (range: 0.2-17.2 years, median age: 3.6 years), ghrelin levels were significantly elevated in the PWS group at any age compared with 84 age and BMI-matched controls. 15 In fact, the highest ghrelin levels in PWS were found in the youngest children. Thus, in their study, the hyperghrelinemia was occurring long before the development of obesity and increased appetite in PWS.…”
Section: Hypogonadismmentioning
confidence: 98%
“…92,93 These recurrent common interstitial deletions measure approximately 5-6 Mb in size and are due to the presence of multiple copies of tandemly repeated sequences at the common breakpoints (BP1, BP2, and BP3) flanking the deleted region. These low copy repeat sequences stretch for approximately 250-400 kb and can cause nonhomologous pairing and aberrant recombination of the 15q11.2-q13 region during meiosis, leading to deletions (causing PWS or AS depending on parental origin), duplications (both maternal and paternal), triplications, and inverted dup (15 can also determine the parental origin in this region and is discussed further below. Although DNA methylation should be a first-line test for diagnosis, it cannot distinguish the molecular class (i.e., deletion, UPD, or ID).…”
Section: Paternal Deletionmentioning
confidence: 99%